WORK PRODUCTIVITY ASSESSED FROM AWARD, WORK EXPENSE, DISCIPLINE, AND EMPLOYEE SATISFACTION STUDY AT THE ENVIRONMENT AND FORESTRY OFFICE OF KLATEN REGENCY - Apriliana Kusuma Dewi; Istiatin Istiatin; Bambang Mursito (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study was to determine whether there is a significant influence between the variables of reward, workload, discipline, and employee satisfaction on work productivity. In addition, it is also to determine whether there is a significant simultaneous influence and which variable is the most dominant in influencing the work productivity of the employees of the Environment and Forestry Office of Klaten Regency. The method used is descriptive quantitative method. The population in this study amounted to 43 employees and the entire population was sampled in this study, where the sampling technique used quota sampling. The data used are primary data and secondary data with data collection techniques: observation, documentation, questionnaire and literature study. The data analysis technique in this study used multiple linear tests. The results of the study can be concluded that: The results of the study can be concluded that: 1) There is an effect of appreciation, workload, discipline, and employee satisfaction simultaneously on work productivity of employees of the Environmental and Forestry Service of Klaten Regency, 2) There is an effect of appreciation on work productivity. for employees of the Environment and Forestry Service Office of Klaten Regency, 3) There is an effect of workload on work productivity of employees of the Office of Environment and Forestry of Klaten Regency, 4) There is an effect of discipline on work productivity of employees of the Office of Environment and Forestry of Klaten Regency, 5) There the influence of employee satisfaction on work productivity of the employees of the Environment and Forestry Service in Klaten Regency Keywords: Work Productivity, Rewards, Workload, Discipline, Employee Satisfaction.